2022
DOI: 10.1097/mcg.0000000000001681
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Remission (NANCY Index) is Superior to Endoscopic Mucosal Healing in Predicting Relapse Free Survival in Patients With Ulcerative Colitis in Clinical and Endoscopic Remission

Abstract: Background: Histologic activity is recognized as an important predictor of relapse in ulcerative colitis (UC) patients. Current treatment targets aim at mucosal healing; however, many patients continue to have histologic activity. Goals: The aim was to assess histologic activity using the validated Nancy histologic index (NHI) score as a predictor of future relapse amongst UC patients in endoscopic and clinical remission. Study: In this retrospective cohort study, UC patients in clinical and endoscopic rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Similar results were reported in a recently published study [ 43 ] of 184 UC patients with a median follow-up of 42 months. Patients with MES 0 and histologic remission (NHI 0) had significantly higher relapse-free rates of survival.…”
Section: Prognostic Values For Clinical Relapse Of Histological Scoressupporting
confidence: 91%
“…Similar results were reported in a recently published study [ 43 ] of 184 UC patients with a median follow-up of 42 months. Patients with MES 0 and histologic remission (NHI 0) had significantly higher relapse-free rates of survival.…”
Section: Prognostic Values For Clinical Relapse Of Histological Scoressupporting
confidence: 91%
“…Despite endoscopic normalization, ongoing active histological activity may be associated with poorer clinical outcomes including higher clinical relapse rates, corticosteroid requirement, hospitalization, colectomy and development of colorectal neoplasia[ 3 - 7 ]. Although histological remission is currently not a formal treatment target by consensus expert-opinion, STRIDE-II guidelines do recommend that formal histological assessment take place to determine the depth of remission and help prognosticate patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment outcome paradigms are shifting in recent years into establishment of deeper objective findings demonstrating complete healing of the bowel in patients with IBD. To date, adult guidelines suggest mucosal/endoscopic healing as the desirable target for patients with UC (3,4), but this may change in the near future given increased interest in the ability of histologic findings to predict disease outcomes, especially in patients without endoscopic inflammation (5,(11)(12)(13). While different histologic indices were developed in adults, they were not validated in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The NHI was also shown to be an important feature that can predict outcomes in patients with IBD. Wang et al (5), for example, showed in UC patients with MES ≤ 1 that an NHI ≤ 1 was the only predictor of clinical relapse (29% vs 64%) during a median follow‐up of 42 months (hazard ratio 4.36, P = 0.002). In our study, 10 patients had complete mucosal healing, and 6 of them had concurrent histological remission (NHI = 0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation